Putative Primo-Vascular System in Rabbit Placenta - Fatma El-Zahraa A. Mustafa (Medical Association of Pharmacopuncture Institute, 2019)
The primo vascular system (PVS) is a very important topic of study nowadays because of their role in transport and regeneration of tissue and in cell migration and cancer metastasis. The PVS was detected in different organs of the rabbit but not in the placenta. In this work, we observe the PVS inside the blood vessels of the placenta for the first time. The main characteristic features of the primo vessels (PVs) from the rabbit placenta were in agreement with the PVS in different organs of animals, including the rod-shaped nuclei and their arrangement. Keywords: inflammatory cell, placenta, primo vascular system, primo vessel, rabbit